Analisis Efektivitas Sistem Pengendalian Internal Barang Perlengkapan Studi Kasus Di Sempoa Tc Dharmahusada Mas - Oktavia Dwi Sheila R; Anna Marina; Fitri Nuraini (Fakultas Ekonomi Universitas PGRI Adi Buana, 2021)
The purpose of this research was to determine the importance of internal control on systems and procedures for supplying stocks at the Sempoa Sip TC Dharmahusada Mas which is one of the current assets in the company in addition to income from paying special fees. To find out whether the systems and procedures at the Sempoa Sipwhich have been running for several years are effective and in accordance with the procedures. Collecting data in this research are interviews, documentation, literature study, primary data, secondary documents. clear enough. However, the division of tasks at the company is still not good because it is only carried out by the admin, namely, the purchasing system, goods receipt system, expenditure system, warehouse has not been effective. This shows that there is no good principle of segregation of functions, namely segregation of duties.